2008
DOI: 10.3747/co.v15i0.270
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Cancer Patients through the Continuum of Care: A View from the Age of Social Networks and Computer-Mediated Communication

Abstract: Almost since its inception, the Internet has been used by ordinary people to connect with peers and to exchange health-related information and support. With the rapid development of software applications deliberately designed to facilitate social interaction, a new era is dawning in which patients and their loved ones can collaboratively build knowledge related to coping with illness, while meeting their mutual supportive care needs in a timely way, regardless of location. In this article, we provide backgroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Most diabetes apps that claimed to include social media features only provided a link to the device’s group page in social networking sites such as Twitter and Facebook. Online health communities have repeatedly demonstrated their value in bringing together cancer patients and survivors to exchange information and support [ 26 ]. While the exact mechanisms by which social relationships affect health remains unclear, nearly 30 years of research has consistently demonstrated that they have a powerful effect on physical and mental health and may extend survival [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most diabetes apps that claimed to include social media features only provided a link to the device’s group page in social networking sites such as Twitter and Facebook. Online health communities have repeatedly demonstrated their value in bringing together cancer patients and survivors to exchange information and support [ 26 ]. While the exact mechanisms by which social relationships affect health remains unclear, nearly 30 years of research has consistently demonstrated that they have a powerful effect on physical and mental health and may extend survival [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Internet-based resources may be ideally suited to address the psychoeducational needs of partners as described herein. Internet-based tools could enable health professionals to effectively incorporate self-help materials that could be downloaded or printed from the Web, as well as leverage interactive multimedia aids such as videos, expert webinars, and online discussion forums to deliver content, provide support, and engage participants [ 28 ]. Moreover, Internet-driven intervention-delivery approaches provide ample flexibility to tailor content to individuals’ needs and offer targeted materials for population subgroups, which are strategies that have been shown to improve intervention outcomes [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Professionally facilitated, Internet-based psychoeducational interventions implemented in diverse populations [ 30 ], including those with cancer [ 28 ], have shown promising results. Intervention platforms such as the Comprehensive Health Enhancement and Support System improve psychosocial outcomes among women with breast cancer [ 57 - 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The internet offers a convenient and cost-efficient way to provide personally tailored health information and services [8,9] and is expected to help reduce social inequalities by providing individuals access to information that might otherwise be inaccessible [10]. However, there is concern that the internet may be perpetuating disparities in access to health services by keeping certain segments of the population, such as seniors, on the sidelines [11].…”
Section: Introductionmentioning
confidence: 99%